Agrarian Sustainability and Its Governance – Understanding, Evaluation, Improvement - BACHEV, Hrabrin; IVANOV, Bodjidar; TOTEVA, Desislava; SOKOLOVA, Emilia (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016DO - 10.14505//jemt.v7.4(16).11, 2017)
Research on agrarian sustainability and its governance is still at the beginning stage due to the “newness” of the problem, emerging new challenges, fundamental modernization during recent years, “lack” of long-term experiences and relevant data, application of narrow (certain form or management level); one-dimensional, unisectorial, normative, without transaction costs etc. approaches. The goal of this paper is to suggest a modern, holistic and practical framework for analyzing and assessing the system of governance of agrarian sustainability. Interdisciplinary frameworks of the New Institutional Economics and Sustainable Development are incorporated and agrarian sustainability property defined, principle mechanisms and modes of governance (institutions, market, private, public, hybrid) of agrarian sustainability classified, and a holistic approach for identifying components and factors, assessing efficiency of governance and sustainability levels, and improving the system of governance presented.